FOG-2, a Heart- and Brain-Enriched Cofactor for GATA Transcription Factors - Lu, Jian-rong (American Society for Microbiology, 1999)
Members of the GATA family of zinc finger transcription factors have been shown to play important roles in the control of gene expression in a variety of cell types. GATA-1, -2, and -3 are expressed primarily in hematopoietic cell lineages and are required for proliferation and differentiation of multiple hematopoietic cell types, whereas GATA-4, -5, and -6 are expressed in the heart, where they activate cardiac muscle structural genes. Friend of GATA-1 (FOG) is a multitype zinc finger protein that interacts with GATA-1 and serves as a cofactor for GATA-1-mediated transcription. FOG is coexpressed with GATA-1 in developing erythroid and megakaryocyte cell lineages and cooperates with GATA-1 to control erythropoiesis. We describe a novel FOG-related factor, FOG-2, that is expressed predominantly in the developing and adult heart, brain, and testis. FOG-2 interacts with GATA factors, and interaction of GATA-4 and FOG-2 results in either synergistic activation or repression of GATA-dependent cardiac promoters, depending on the specific promoter and the cell type in which they are tested. The properties of FOG-2 suggest its involvement in the control of cardiac and neural gene expression by GATA transcription factors.